EXPLORING HEAVY METAL PRESENCE IN LYCOPERSICUM ESCULENTUM L. AND ITS SOIL SAMPLES : PROXIMITY TO RIVER HASDEO AND AHIRAN IN KORBA DISTRICT, CHHATTISGARH - Gayatri Sahu, Rita Bajpai (Chelonian Research Foundation, 2024)
This study investigates the presence of heavy metals in Lycopersicum esculentum L. (tomato) and its associated soil samples in the vicinity of River Hasdeo and Ahiran in Korba District, Chhattisgarh. Heavy metal contamination in agricultural products and soil poses significant environmental and health risks. In this research, samples were collected and analyzed for the concentrations of various heavy metals. The analysis was performed using triplicate measurements, and the results were expressed as mean values with standard deviations. The mean concentrations of metals in both tomato and soil samples were calculated. The reported mean concentration of heavy metals are (0.216-1.057) , (0.125- 0.530) (0.444 -0.823) (0.104-1.247) (0.012-0.053) in mg/kg for Zn, Cu, Mn, Fe & Pb respectively for tomato plant. And mean conc. of heavy metals in soil reported as (0.012-0.167) (0.124- 0.044) (0.067- 0.067) (0.098-0.461) (0.012-0.074) in mg\kg for Zn, Cu, Mn, Fe & Pb respectively. The Pearson coefficient correlation between heavy metals also discussed in this research paper. The findings of this study provide valuable comprehensions of heavy metal impurity in agricultural produce and soil in the studied region, aiding in the development of appropriate mitigation strategies to safeguard environmental and human health. Keywords - Standard deviations, Heavy metals, Vicinity